Activated complement factor 3 is associated with liver fat and liver enzymes: the CODAM study. (16th April 2013) - Wlazlo, Nick; van, Marleen M. J.; Ferreira, Isabel; Jansen, Eugene H. J. M.; Feskens, Edith J. M.; van der, Carla J. H.; Schalkwijk, Casper G.; Bravenboer, Bert; Stehouwer, Coen D. A.
Abstract Background The complement system may be involved in the pathogenesis of alcoholic and nonalcoholic liver disease, although studies in humans are scarce. For this reason, we investigated whether circulating levels of activated complement factor 3 (C3a) were associated with hepatic steatosis and hepatocellular damage. Materials and methods Plasma C3a, aspartate aminotransferase (AST), alanine aminotransferase (ALT) and gamma‐glutamyl transferase (GGT) were determined in 523 individuals (61% men, age 59 ± 7 years). Liver enzymes (LEs) were standardized and compiled into a LE score. Liver fat content was estimated using a predictive equation that has recently been validated with magnetic resonance spectrometry. Cross‐sectional associations between C3a and liver fat or LE s were investigated with multiple linear regression analyses, stratified in no‐to‐moderate vs. heavy alcohol consumers (men: > 30 g/day; women: > 20 g/day). Results C3a was associated with liver fat percentage both in the no‐to‐moderate (β = 0·223; 95%CI 0·036; 0·409) and in the heavy alcohol consumers (β = 0·632; 95%CI 0·259–1·004; P‐interaction = 0·047). C3a was also associated with the LE score in heavy alcohol consumers (β = 0·917; 95%CI 0·443–1·392), but not in no‐to‐moderate alcohol consumers (β = 0·042; 95%CI −0·198 to 0·281; P‐interaction = 0·001). Conclusions C3a levels, as a marker of complement activation, were associated with liver fat content and hepatocellular injury, at least in subjects who consume considerable amounts of alcohol daily.